Viability markers for determination of desiccation tolerance and critical stages during dehydration in Selaginella species. (21st March 2022) - Alejo-Jacuinde, Gerardo; Kean-Galeno, Tania; Martínez-Gallardo, Norma; Tejero-Díez, J Daniel; Mehltreter, Klaus; Délano-Frier, John P; Oliver, Melvin J; Simpson, June; Herrera-Estrella, Luis
Abstract: While most plants die below a threshold of water content, desiccation-tolerant species display specific responses that allow them to survive extreme dehydration. Some of these responses are activated at critical stages during water loss and could represent the difference between desiccation tolerance (DT) and death. Here, we report the development of a simple and reproducible system to determine DT in Selaginella species. The system is based on exposure of excised tissue to a dehydration agent inside small containers, and subsequent evaluation for tissue viability. We evaluated several methodologies to determine viability upon desiccation including: triphenyltetrazolium chloride (TTC) staining, the quantum efficiency of PSII, antioxidant potential, and relative electrolyte leakage. Our results show that the TTC test is a simple and accurate assay to identify novel desiccation-tolerant Selaginella species, and can also indicate viability in other desiccation-tolerant models (i.e. ferns and mosses). The system we developed is particularly useful to identify critical points during the dehydration process. We found that a desiccation-sensitive Selaginella species shows a change in viability when dehydrated to 40% relative water content, indicating the onset of a critical condition at this water content. Comparative studies at critical stages could provide a better understanding of DT mechanisms and unravel insights into the key responses to survive desiccation. Abstract : A simple and efficient system to determine critical stages during dehydration in Selaginella that can be applied to identify desiccation-tolerant plants.